2013
DOI: 10.2310/7750.2012.12022
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mycosis Fungoides with Bexarotene Results in Remission of Diffuse Plane Xanthomas

Abstract: Bexarotene led to the clearing of the cutaneous lesions of cutaneous T-cell lymphoma and plane xanthomas. This may be due to an effect of bexarotene on the aberrant T cells that may cause xanthomatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Cladribine has been used successfully in Langerhans cell histiocytosis of different types including plane xanthoma [ 10 ]. There are case reports on regression of DNPX during treatment (of associated disorders) with cyclosporine A [ 11 ] or bexarotene [ 12 ]. DNPX can be treated by ablative lasers such as erbium-YAG laser [ 13 ][ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cladribine has been used successfully in Langerhans cell histiocytosis of different types including plane xanthoma [ 10 ]. There are case reports on regression of DNPX during treatment (of associated disorders) with cyclosporine A [ 11 ] or bexarotene [ 12 ]. DNPX can be treated by ablative lasers such as erbium-YAG laser [ 13 ][ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both are nuclear receptors which regulate the transcription of apoE and ABCA1 (Liang et al, 2004; Zhao et al, 2014) by forming heterodimers with each other, or with other nuclear receptors such as retinoid acid receptor (RAR), peroxisome proliferator-activated receptor γ (PPARγ), thyroid hormone receptor (TR) or vitamin D receptor (VDR) as transcriptional co-regulators (Chawla et al, 2001; Evans and Mangelsdorf, 2014; Sussman and de Lera, 2005; Szanto et al, 2004). Of importance, bexarotene, an RXR agonist, has been reported to improve cognitive function as well as reduce brain amyloid-β (Aβ) levels in an Alzheimer’s disease (AD) mouse model (Cramer et al, 2012), although it was originally approved by the U.S. Food and Drug Administration (FDA) to treat cutaneous T-cell lymphoma (Gregoriou et al, 2013; Mehta et al, 2012; Scarisbrick et al, 2013; Vakeva et al, 2012). However, the effects of bexarotene on AD are controversial due to conflicting results from different investigators (Fitz et al, 2013; LaClair et al, 2013; Price et al, 2013; Tesseur et al, 2013; Veeraraghavalu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Physical approaches and surgical resection are too invasive for general lesions. 6 Gregoriou et al 7 reported that bexarotene was effective for treating DPX. Oral probucol has also been proposed.…”
Section: Discussionmentioning
confidence: 99%